2005
DOI: 10.1534/genetics.105.044057
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Functions of Yeast Genes Support the Duplication, Degeneration and Complementation Model for Gene Duplication

Abstract: Gene duplication is often cited as a potential mechanism for the evolution of new traits, but this hypothesis has not been thoroughly tested experimentally. A classical model of gene duplication states that after gene duplication one copy of the gene preserves the ancestral function, while the other copy is free to evolve a new function. In an alternative duplication, divergence, and complementation model, duplicated genes are preserved because each copy of the gene loses some, but not all, of its functions th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 40 publications
1
80
3
Order By: Relevance
“…In the duplication, degeneration, and complementation (DDC) model, duplicated genes each lose one of the original functions and together retain the entire set of ancestral functions (47,48), whereas in the specialization model the divergence of functions among paralogs also involves the accumulation of advantageous mutations in at least one of the duplicated genes, enabling it to outperform the ancestral gene (10,11,49,50). An earlier study investigating the nonduplicated Orc1 from Saccharomyces kluyveri concluded that Orc1 subfunctionalized through the DDC pathway, based on the ability of SkOrc1 to complement both orc1 and sir3 mutations in S. cerevisiae (34). However, we suggest that although the SIR3-ORC1 gene pair did subfunctionalize, it is more likely a case of specialization.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In the duplication, degeneration, and complementation (DDC) model, duplicated genes each lose one of the original functions and together retain the entire set of ancestral functions (47,48), whereas in the specialization model the divergence of functions among paralogs also involves the accumulation of advantageous mutations in at least one of the duplicated genes, enabling it to outperform the ancestral gene (10,11,49,50). An earlier study investigating the nonduplicated Orc1 from Saccharomyces kluyveri concluded that Orc1 subfunctionalized through the DDC pathway, based on the ability of SkOrc1 to complement both orc1 and sir3 mutations in S. cerevisiae (34). However, we suggest that although the SIR3-ORC1 gene pair did subfunctionalize, it is more likely a case of specialization.…”
Section: Discussioncontrasting
confidence: 55%
“…Nonduplicated orthologs of Orc1 and Sir3 display more sequence similarity to ScOrc1 than to ScSir3, and this accelerated sequence divergence in Sir3 has led to the hypothesis that the silencing function of Sir3 arose through neofunctionalization (29). However, others have argued that Orc1 and Sir3 subfunctionalized (34).…”
mentioning
confidence: 99%
“…This is conceptually similar to no-go decay, which is the rapid endonucleolytic cleavage of mRNAs with an internally stalled ribosome (25). Furthermore, nonstop decay and no-go decay require the paralogs SKI7 and HBS1, respectively (22,25,39). Given this similarity, we considered the possibility that Rrp44p may be the endonuclease responsible for no-go decay and that our nonstop mRNAs with stalled ribosomes at their 3′ ends were also susceptible to no-go decay.…”
Section: Either the Endo-or Exonuclease Activity Of Rrp44p Can Efficimentioning
confidence: 96%
“…The relative probabilities of neofunctionalization and subfunctionalization remain unclear. However, growing evidence suggests subfunctionalization is common (Van Hoof 2005).…”
mentioning
confidence: 99%